An Interdisciplinary Approach in Preparing Future Music Teachers for Professional Activities: a Methodological Aspect: Array - Sirotkina, Zhanna (Journal of Danubian Studies and Research, 2020)
The professional activities of a music teacher are very diverse and diverse. Therefore, there is an urgent problem of creating unique methods of preparing students for future musical and pedagogical activities. In particular, the creation of the necessary conditions such as the presence of system-integrative connections, the formation of methodological competence among students, the development of a broad methodological environment as the basis for students to master the complex of methods of musical training and education in order to organize various types of musical activity of students. It should also be taken into account that the process of methodological preparation as an integrated system of relations between teachers and students is carried out under the influence of many factors, each of which plays a specific role, determined by its content and orientation of the impact. A promising way to introduce future teacher-musicians into the training process is the following principles: systemicity, integrativity, determinism, emergence, interaction between a pedagogical university and a school, and the like.